2019
DOI: 10.3390/su11226187
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Spatial Distribution of Transportation Accessibility in the Regions Involved in the Belt and Road Initiative

Abstract: The Belt and Road Initiative (BRI) is a Chinese strategy, proposed to strengthen the connectivity and cooperation among BRI countries. Under this circumstance, many transportation projects are planned to be carried out, which means the transportation accessibility evaluation is of significance in providing valuable suggestions for transportation construction. This research established a global transportation accessibility index (GTAI) model in the BRI region using raster data. Based on its gridded outputs, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…In 2013, China's president, Xi Jinping, proposed building the "Silk Road Economic Belt" and the "21st Century Maritime Silk Road", also known as the "Belt and Road Initiative" (BRI). This initiative involves infrastructure construction and also seeks to establish a widespread setup for economic cooperation, policy cooperation, trade and business collaboration, and everlasting cultural cooperation [1,2]. Through open, transparent, and efficient cooperation, participating countries are likely to avail themselves of substantial mutual economic benefits from the Belt and Road Initiative.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, China's president, Xi Jinping, proposed building the "Silk Road Economic Belt" and the "21st Century Maritime Silk Road", also known as the "Belt and Road Initiative" (BRI). This initiative involves infrastructure construction and also seeks to establish a widespread setup for economic cooperation, policy cooperation, trade and business collaboration, and everlasting cultural cooperation [1,2]. Through open, transparent, and efficient cooperation, participating countries are likely to avail themselves of substantial mutual economic benefits from the Belt and Road Initiative.…”
Section: Introductionmentioning
confidence: 99%
“…In order to visualize the transportation accessibility of the BRI region using grid cells (Lobyrev et al, 2018). Shi et al (2019) suggested a global accessibility index. The density of the roads, railroads, and waterways is calculated and then combined to produce the impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The average of the transportation convenience and density indices is known as the global accessibility index (Liu, 2018). Grid-based or area-based assessment approaches have been utilized by both Chhetri et al (2018) and Shi et al (2019), but little has been known about the connectivity linkages in transportation networks. Derudder et al's (2018) study of the six BRI routes' cities' centrality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study it was noted that people should be able to reach their destinations with minimum limitations or delays, regardless of the direction of their travel [14]. It is evident from the available literature that the notion of accessibility includes the end-user, the transport system, travel time, and land use [15]. Nevertheless, the issue is even more complex because accessibility may depend on additional factors such as leisure activities, housing, wellbeing, and available health services [16].…”
Section: Literature On the Subject Of Social Elements Of Transportationmentioning
confidence: 99%